PEMBERDAYAAN MASYARAKAT KAMPUNG CIJANTUR UNTUK MENDAPATKAN AIR BERSIH MELALUI PENERAPAN SALURAN AIR TANPA LISTRIK DENGAN PEMBAGUNAN BENDUNGAN - Sari, Santika; Fajriah, Nur; Saputra, Noverdo; Maulana, Wahyu; Hendradi, Alif; Syifa, Annisa; Fadhillah, Azriel (Jurnal Abdi Masyarakat, 2021)
Cijantur Village is one of the villages located in the highlands of Rabak Village, Rumpin District, Bogor Regency. This village is one of the areas experiencing many problems, starting from the access road to this village in poor condition, the main occupation of the residents who do not meet their daily needs and the difficulty of getting clean water because the water source is very far away. Of the many problems faced by Cijantur Village, the most difficult problem for the people of this village is the difficulty of getting clean water because the distance of water sources is very far, especially during the COVID-19 pandemic like now cleanliness has become a very priority thing to avoid from viral exposure. Therefore, we intend to help the people of Cijantur village, Rabak Village, Rumpin District, Bogor Regency to get clean water by building water channels without electricity by building water dams. Clean water is distributed by making water dams at the location of the water source and piped to a clean water storage location that can be accessed by residents. The distribution of water from water sources to residents' water storage locations uses water pressure techniques and differences in water levels. This water distribution technology can be applied to areas where the population has limited technical skills, because the maintenance required is simple and without having to pay electricity costs. The steps of activities that will be carried out in this program are: (1) Program socialization, (2) Preparation of equipment and materials, (3) Making water dams near water sources, (4) Implementation of connecting output pipes from water dams towards the final storage tower (5) Assistance, and (6) Monitoring and evaluation of the implementation of activities. Based on the results of the activities that have been carried out, water can be channeled properly to the final storage tower which is close to the residential location of residents. This can help the residents of Cijantur Village to get clean water so that it can have an impact on the health of residents who are more secure with clean water.